Effect of geometrical parameters on the flexural properties of sandwich structures with 3D-printed honeycomb core and E-glass/epoxy Face-sheets. (October 2021) - Pirouzfar, Sabah; Zeinedini, Afshin
Abstract: Honeycomb structures are extensively used in the different applications. These structures are mainly made of Aluminum and Nomex materials. Nowadays, additive manufacturing (AM) technology has created a revolution in the manufacturing of different structures. In this paper, the honeycomb structure was manufactured using a fused filament fabrication (FDM) 3D printer. The effect of different geometrical parameters on the flexural properties of the 3D-printed honeycomb structures and their sandwich panels with the face-sheets made of E-glass/epoxy laminates were investigated. Three cell wall thicknesses, i.e., 1, 1.5 and 2 mm, were considered for the honeycomb structures. Moreover, two arrangements, i.e., vertical and horizontal directions, were regarded for the honeycomb structures. One of the disadvantages of the vertical honeycomb core panels is the weak bond between the core and the skins. Hence, the effect of printed thin layers between the skins and the vertical honeycomb core on the flexural properties of panels was also evaluated. Besides, the stress analysis of the samples was performed by a finite element simulation. The results showed that the structure consisting of the horizontal honeycomb core with wall thickness of 1.5 mm has the maximum normalized energy absorption. Comparing the obtained results with the available data in the literature manifested that the flexural properties of the honeycomb core sandwich structures are significantly improved by changing its core system from the Nomex and Aluminum materials to the printed system.